Space STEM Education Guide for Global Positioning System Total Electron Content (GPS TEC) - Chollada Pansong; Thanapon Keokhumcheng; Patiphan Sumniang; Wishapol Sittichai; Canjie Huang; Prasert Kenpankho (My University, 2024)
This research focuses on designing a Space Science teaching model using a Science, Technology, Engineering, and Mathematics (STEM) education approach, specifically applying satellite technology in the Global Navigation Satellite System (GNSS), with an emphasis on Global Positioning System (GPS) satellites. The goal is to propose a new model in STEM education in Space Science by teaching GPS Total Electron Content (GPS TEC) variations in the ionosphere layer resulting from environmental changes on Earth, known as Lithosphere-Atmosphere-Ionosphere Coupling (LAIC). The teaching model was designed, named SPACE (S: Studying the problem, P: Planning and carrying out investigations, A: Analyzing and interpreting data, C: Critical thinking, Creative thinking, Collaborating, Communicating, and E: Evaluating, and Summarizing), serves as a guide for instructional management steps. The model was evaluated by five experts with at least 10 years of experience in Space Science. The evaluation of the appropriateness of the model for use as a teaching guideline resulted in the highest level of suitability $(\bar{x}= \mathbf{4.87},\ \mathbf{SD} =\mathbf{0.40})$.
Keywords: Ionosphere and magnetosphere dynamics; Solar and Space Plasma Dynamics; Earthquake Detection and Analysis